Adaptasi Ekonomi Pengusaha Agribisnis Tahu dalam Menghadapi Kenaikan Harga Kedelai di Kabupaten Banjar - Yusuf Azis (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
This research was aimed to determine economic adaptation options that were done by tofu agribusinessmen and how much the effect of these economic adaptation choices to the cost, revenue, profit and feasibility of this business. The results showed that the significant increase of soybeans price caused tofu agribusinessmen did economic adaptations by reducing number of soybeans they bought, decreasing tofu production, maintaining size and quality of tofu, and increasing selling price of tofu. By doing those things, total cost, revenue, profit and feasibility of business were decreased by Rp 81,000, Rp 6,435,000, Rp 6,354,000 and 0.03 respectively.  However, this business was still feasible to be run.